MathematicsIf p(x)= x 3 − x 2 +x+1,   then value of p(1)+p(-1) is ____.

If p(x)= x 3 x 2 +x+1,   then value of p(1)+p(-1) is ____.


    Fill Out the Form for Expert Academic Guidance!l



    +91



    Live ClassesBooksTest SeriesSelf Learning



    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    If p(x)= x 3 x 2 +x+1,   then value of p(1)+p(-1) is 0.
    Given a polynomial,
    p(x)= x 3 x 2 +x+1   Substitute x = 1 in the given polynomial, we get,
    p(1)= 1 3 1 2 +1+1 p(1)=11+1+1 p(1)=2  
    Substitute x = -1 in the given polynomial, we get,
    p(1)= 1 3 1 2 1+1 p(1)=111+1 p(1)=2  
    Then,
      p(1)+p(1)=2+ 2 p(1)+p(1)=0  
    The value of p(1)+p(1)   is 0.
     
    Chat on WhatsApp Call Infinity Learn

      Talk to our academic expert!



      +91


      Live ClassesBooksTest SeriesSelf Learning




      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.